The Olympians among us - Abd Razak, Dzulkifli (2009)
TWO personalities captured our imagination this past week, the dynamic Datuk Seri Idris Jala and the late Senator Professor Datuk Dr Ismail Md Salleh who was equallydynamic. Idris, who was handpicked in December 2005 to helm Malaysia Airlines as its managing director and chief executive officer, is now a cabinet member. A graduate of Universiti Sains Malaysia, Idris made a name for himself while working for Shell where he spent a good 23 years as an industrial relations officer of Sarawak Shell Berhad, then as the head of staff development and was on assignment as human resources planner in the Netherlands.